2023
DOI: 10.1039/d3mh00629h
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-robust, high-adhesive, self-healing, and photothermal zwitterionic hydrogels for multi-sensory applications and solar-driven evaporation

Abstract: A new class of high-performance and multifunctional zwitterionic hydrogels were designed based on the incorporation of polydopamine-coated liquid metal nanoparticles into poly(sulfobetaine methacrylate) zwitterionic hydrogels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…19 Therefore, autonomous self-healing with multifunctionalities would be of great interest. 20 Jing et al have successfully developed a highly conductive organohydrogel electrode which exhibits autonomous self-healing via reversible chemical bonds with the incorporation of stretchability and temperature adaptability. 21…”
Section: Sh Materials: a Marvel In Materialsmentioning
confidence: 99%
“…19 Therefore, autonomous self-healing with multifunctionalities would be of great interest. 20 Jing et al have successfully developed a highly conductive organohydrogel electrode which exhibits autonomous self-healing via reversible chemical bonds with the incorporation of stretchability and temperature adaptability. 21…”
Section: Sh Materials: a Marvel In Materialsmentioning
confidence: 99%
“…LM/polymer materials showcase superior flexibility and mechanical reliability in comparison with traditional rigid metal–polymer composites. 6,23,35,36 In the majority of the research studies, the distribution of LMs within a polymer matrix is achieved through the mechanical mixing of LMs and uncured polymers. For instance, Zhang et al 37 utilized 55% gallium-based LMs and 15% copper particles as fillers to make a composite with uncured Ecoflex, resulting in TIMs with a κ value of 3.94 W m −1 K −1 and Young's modulus of 699 kPa.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the isotropically extensible deformation of LM@PDA, the mechanical properties of zwitterionic hydrogels have been well improved. 19 Zwitterionic microgels have been cross-linked into zwitterionic hydrogel networks to improve their mechanical properties. The destruction and reconstruction of the electrostatic interaction between the microgels and hydrogel could effectively dissipate energy and avoid stress concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Zwitterionic molecules contain both anionic and cationic groups, and hydrogels that are composed of zwitterionic polymers usually exhibit excellent biocompatibility and hydrophilicity and have been widely used in biological fields. And it is also reported that zwitterionic hydrogels can show conductivity, attributed to the effective ion channels induced by their inner zwitterionic groups. , With these properties, the zwitterionic hydrogels are potential materials for fabricating strain sensors, electronic skins, and intelligent wearable devices. However, zwitterionic hydrogels often suffer from poor mechanical properties, with fracture strengths lying in the kPa range and toughness around 1 MJ/m 3 or lower, , which severely limits their further applications. Higher mechanical properties can improve the operability of hydrogels in the fabrication of sensors and maintain the stability of hydrogel-based devices upon extreme mechanical stress during practical use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation